Chemical stability of active ingredients in diluted veterinary disinfectant solutions under simulated storage conditions - Rhee, Chae Hong; Lee, Hye-sook; Yun, Hyeong-jun; Lee, Ga-Hee; Kim, Su-Jeong; Song, Sok; Lee, Myoung-Heon; Her, Moon; Jeong, Wooseog (Frontiers in Chemistry, 2023)
Introduction: The product labels of veterinary disinfectants specify their expiration dates to prevent the use of outdated products, as these may result in disinfection and biosecurity failures during outbreak situations. However, a clear standard for the storage conditions of diluted disinfectant solutions has not yet been established, and the effects of storage conditions have scarcely been investigated. To fill this research gap, our study examined the stability of the active ingredients of diluted veterinary disinfectants based on their change in concentrations when stored at various temperatures for various time periods. Methods: Twenty veterinary disinfectants effective against either foot-and-mouth disease or avian influenza viruses were selected. The disinfectants were diluted to effective concentrations following the manufacturer’s instructions. Using selective analytical techniques, the concentrations of the active ingredients of the samples that had been stored for varying intervals at different temperatures (4, 20, 30, and 45°C) were determined. These samples included soaps and detergents, acids, oxidizing agents, aldehydes, and copper compounds. The active ingredient concentrations of two of the samples were determined following freezing/thawing cycle, to establish their stability when exposed to simulated winter conditions. Results: Our results showed that most of the active ingredients had concentrations of 90% or greater of their initial concentrations, indicating ≥90% stability over a 21-day period under the experimental storage conditions. However, there were some exceptions. Glutaraldehyde, formaldehyde, and malic acid are over 90% stable at ≤ 30°C for 21 days, but their concentrations decreased to below 90% of their initial concentrations at 45°C, indicating a decline in stability when stored at 45°C for 21 days. The concentrations of potassium peroxymonosulfate and peracetic acid rapidly declined with increasing time and temperature to less than 90% of their initial concentrations. Discussion: Based on our findings, we propose that diluted disinfectant solutions should preferably be prepared daily. However, if the daily preparation of a diluted disinfectant solution is not feasible, then our results can be used as a reference, providing basic scientific data on the chemical stability of diluted disinfectant solutions commonly used in the veterinary field, thus indicating suitable storage conditions.